Effects of Dietary Iron Levels on the Production Performance, Nutrient Digestibility, Blood Biochemistry, and Meat and Fur Quality of Growing Rex Rabbits - Jiali Chen; Jiyuan Wang; Lei Liu; Fuchang Li (Animals)
The objective of this study was to explore the effects of dietary iron (Fe) levels on the production performance, nutrient digestibility, blood biochemistry, and meat and fur quality of growing Rex rabbits. Two hundred 3-month-old Rex rabbits were randomly allocated to five groups, each with forty replicates. Rabbits were fed a basal diet supplemented with varying levels of Fe (0, 20, 40, 80, and 160 mg/kg) in the form of ferrous sulfate monohydrate. The analyzed Fe concentrations in the diets were 8.2, 25.4, 49.1, 85.6, and 178.7 mg/kg, respectively. Over a 35-day trial period, rabbits supplemented with 40 mg/kg Fe showed a markedly increased average daily feed intake, average daily gain, and fur area compared to the control group (p < 0.05). The addition of 20 and 40 mg/kg Fe markedly improved the digestibility of crude protein and nitrogen (p < 0.05). Additionally, 80 mg/kg Fe supplementation significantly increased the redness of the longissimus dorsi muscle 30 min postmortem (p < 0.05). Dietary Fe addition also significantly elevated serum concentrations of Fe and copper (p < 0.05) while decreasing the total Fe-binding capacity (p < 0.05). In conclusion, dietary Fe supplementation boosted growth performance, protein and nitrogen digestibility, Fe stores, and meat and fur quality in Rex rabbits. Specifically, 40 mg/kg Fe (diet Fe content of 49.1 mg/kg) improved growth performance, nutrient digestibility, and fur quality, while 80 mg/kg Fe (diet Fe content at 85.6 mg/kg) was optimal for enhancing meat quality.